Role of Human-Induced Pluripotent Stem Cell-Derived Spinal Cord Astrocytes in the Functional Maturation of Motor Neurons in a Multielectrode Array System. (21st October 2019) - Taga, Arens; Dastgheyb, Raha; Habela, Christa; Joseph, Jessica; Richard, Jean-Philippe; Gross, Sarah K.; Lauria, Giuseppe; Lee, Gabsang; Haughey, Norman; Maragakis, Nicholas J.
Abstract: The ability to generate human-induced pluripotent stem cell (hiPSC)-derived neural cells displaying region-specific phenotypes is of particular interest for modeling central nervous system biology in vitro. We describe a unique method by which spinal cord hiPSC-derived astrocytes (hiPSC-A) are cultured with spinal cord hiPSC-derived motor neurons (hiPSC-MN) in a multielectrode array (MEA) system to record electrophysiological activity over time. We show that hiPSC-A enhance hiPSC-MN electrophysiological maturation in a time-dependent fashion. The sequence of plating, density, and age in which hiPSC-A are cocultured with MN, but not their respective hiPSC line origin, are factors that influence neuronal electrophysiology. When compared to coculture with mouse primary spinal cord astrocytes, we observe an earlier and more robust electrophysiological maturation in the fully human cultures, suggesting that the human origin is relevant to the recapitulation of astrocyte/motor neuron crosstalk. Finally, we test pharmacological compounds on our MEA platform and observe changes in electrophysiological activity, which confirm hiPSC-MN maturation. These findings are supported by immunocytochemistry and real-time PCR studies in parallel cultures demonstrating human astrocyte mediated changes in the structural maturation and protein expression profiles of the neurons. Interestingly, this relationship is reciprocal and coculture with neurons influences astrocyte maturation as well. Taken together, these data indicate that in a human in vitro spinal cord culture system, astrocytes support hiPSC-MN maturation in a time-dependent and species-specific manner and suggest a closer approximation of in vivo conditions. Stem Cells Translational Medicine   2019;8:1272&1285 : Abstract : We describe a fully human, spinal cord-specific, coculture platform with human-induced pluripotent stem cell-derived motor neurons and astrocytes for multielectrode array recording. We show that human-induced pluripotent stem cell-derived motor neurons/human-induced pluripotent stem cell-derived astrocytes bidirectional morphological and molecular maturation is reflected by electrophysiological recordings with multielectrode array recording.